Labour markets in Poland and Hungary five years from the start of transition: Evidence from monthly data - Holger Brauer; Martin Falk; Martin Raiser (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
This paper presents error correction estimates of a simple interdependent model of the labour market using monthly data over 1990-1994 for the industrial sector in Poland and Hungary. The aim is to investigate three issues in the performance of labour markets during transition. First, is there a stable labour market equilibrium or do high unemployment rates across the region indicate hysteresis? Second, has the intensity of employment adjustment increased with progress in institutional reforms that strengthened corporate governance at the enterprise level? Third, what governs the evolution of real wages and to what extent is there evidence for strong insider power in the labour market? The results reveal striking differences between Poland and Hungary. The former exhibits hysteresis and evidence for considerable insider power while the latter has experienced adjustment towards a stable labour market equilibrium. The intensity of adjustment, however, is high in both countries over the sample period and fails to respond to the initiation of institutional reforms.
Keywords: J20; P52; 330; Hysteresis; Adjustment Intensity; Insider Power; Arbeitsmarkt; Wirtschaftliche Anpassung; Hysteresis; Insider-Outsider-Modell; Institutioneller Wandel; Schätzung; Polen; Ungarn